Preparation of carrot halwa with Aspartame and storage - Patil, Madhav Raghunath (Indian Journal of Dairy Science, 2017)
A study was conducted to develop low calorie carrot halwa by replacing 5 %, 10 %, 15 % and 20 %sugar with Aspartame. Partial replacement of 10% sugar scored highest in sweetness perception and resembled in sensory properties with the sucrose sweetened carrot halwa used as control. Storage studies at 10 ÂºC revealed that aspartame sweetened carrot halwa resembled the control carrot halwa in retaining the sensory profile, but showed rise in acidity and microbial load. HPLC analysis of aspartame sweetened low calorie carrot halwa samples showed no degradation of aspartame up to 3rd day of storage but at 5th day L-phenylalanine and 2,5-diketopiperazine were identified in all the samples containing Aspartame.